Das diferenças e outros demônios... : o realismo mágico da alteridade na educação - Ribetto, Anelice Astrid (2006)
This paper about my research work- is aim to analyze radically some narratives and questions concerning the ways people negotiate different languages, perceptions, and logical perspectives about the world during daily life at schools. These different interpretations about what actually is happening every day in the narrative format; are seriously questioning some pedagogical, political and epistemological standpoints which are focus in a logic of seeing human beings as equals and which does not show space (or do it in a hostile way) to the others (who are not able to fit in the standard model). This hostile hospitality take place in numerous space/temporal situations at school and is clearly seen as a quote of tolerance but is not considering differences as part of reality; that needs to be comprehend and accepted as different ways of thinking, believing, living or creating the world. So many times, tolerance appears dressed colourfully as Scholar inclusion .